Redistribution of CO at the Location of the CO Ice Line in evolving Gas and Dust Disks - Stammler, Sebastian Markus; Dullemond, Cornelis (Arxiv, 2017)
Context. Ice lines are suggested to play a significant role in grain growth and planetesimal formation in protoplanetary disks. Evaporation fronts directly influence the gas and ice abundances of volatile species in the disk and therefore the coagulation physics and efficiency and the chemical composition of the resulting planetesimals. Aims. In this work we investigate the influence of the existence of the CO ice line on the particle growth and on the distribution of CO in the disk. Methods. We include the possibility of tracking the CO content and/or other volatiles in particles and in the gas in our existing dust coagulation and disk evolution model and developed a method for evaporation and condensation of CO using the Hertz-Knudsen equation. Our model does not include fragmentation, yet, which will be part of further investigations. Results. We find no enhanced grain growth just outside the ice line where the particle size is limited by radial drift. Instead we find a depletion of solid material inside the ice line which is solely due to evaporation of the CO. Such a depression inside the ice line may be observable and may help to quantify the processes described in this work. Furthermore, we find that the viscosity and diffusivity of the gas heavily influence the re-distribution of vaporized CO at the ice line and can lead to an increase in the CO abundance by up to a factors of a few in the region just inside the ice line. Depending on the strength of the gaseous transport mechanisms the position of the ice line in our model can change by up to 10 AU and consequently, the temperature at that location can range from 21 K to 23 K.